Prognostic significance of neutrophil to lymphocyte ratio in patients with metastatic breast cancer on the background of eribulin therapy - A. V. Zyuzyukina; V. A. Komissarova; N. O. Popova; V. E. Goldberg; R. A. Zukov (ABV-press, 2022)
Background. The neutrophil to lymphocyte ratio (NLR) is a prognostic marker in various carcinomas, including breast cancer. The NLR reflects the balance of systemic immunity and is associated with survival in patients with solid tumors.Aim. This study retrospectively evaluated the significance of the NLR and the absolute lymphocyte count in patients with breast cancer who received eribulin therapy.Materials and methods. The prognostic significance of the NLR and the absolute lymphocyte count in 33 patients with metastatic breast cancer treated with eribulin in 2020-2021 was analyzed.Results. The median follow-up time for patients was 9 [6; 15] months. Twenty-six of 33 (78.8 %) patients progressed. Seven of 33 (21.2 %) patients were censored due to therapy discontinuation, complete discontinuation after 1 course was required in 3 (9.1 %) patients and was associated with the development of hematological toxicity: 1 (3 %) case of a combination of grade 3 leucopenia and grade 3 thrombocytopenia, 2 (6 %) cases of grade 3 neutropenia. According to the analysis results, the NLR was a statistically significant risk factor for progression in patients on eribulin therapy, both without taking into account the influence of other factors (univariate model) and with the underlying influence of the absolute neutrophil count and the absolute lymphocyte count: hazard ratio (95 % confidence interval) was 1.21 [1.04; 1.41], p = 0.015 and 1.30 [1.07; 1.57], p = 0.008, respectively. There was no statistically significant effect of the absolute neutrophil count and the absolute lymphocyte count in both univariate and multivariate models. To illustrate the impact of SNL on the onset of progression, patients were divided into two subgroups based on median SNL: SNL˂ 2.46 and SNL ≥2.46. The median survival in patients with SNL ≥2.46 was 9 months, and in patients with SNL˂ 2.46 it was 15 months.Conclusion. The results of the pilot study state the NLR is a potential prognostic marker of long-term treatment with eribulin for patients with metastatic breast cancer, and can be used in clinical practice.